2020
DOI: 10.1021/acs.est.0c00805
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Anthropogenically Influenced Isoprene Oxidation in Southeastern United States and Central Amazon

Abstract: Anthropogenic emissions alter secondary organic aerosol (SOA) formation chemistry from naturally emitted isoprene. We use correlations of tracers and tracer ratios to provide new perspectives on sulfate, NO x, and particle acidity influencing isoprene-derived SOA in two isoprene-rich forested environments representing clean to polluted conditionswet and dry seasons in central Amazonia and Southeastern U.S. summer. We used a semivolatile thermal desorption aerosol gas chromatograph (SV-TAG) and filter samplers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 97 publications
1
32
0
2
Order By: Relevance
“…3.1), the inclusion of the recent findings from the chamber study (D'Ambro et al, 2019) improved the model simulation. One possible explanation is different IEPOX-SOA molecular components between the Southeast US and the Amazon, however the reported composition is similar for both locations (Yee et al, 2020) . This new approach also changed IEPOX as shown in Sect 3.1.…”
Section: Seac4rsmentioning
confidence: 85%
“…3.1), the inclusion of the recent findings from the chamber study (D'Ambro et al, 2019) improved the model simulation. One possible explanation is different IEPOX-SOA molecular components between the Southeast US and the Amazon, however the reported composition is similar for both locations (Yee et al, 2020) . This new approach also changed IEPOX as shown in Sect 3.1.…”
Section: Seac4rsmentioning
confidence: 85%
“…With respect to the choice of an extraction solvent, acetonitrile is to be preferred above methanol, because of the risk of methylation artefacts in acidic medium, e.g., [32]. An online measurement technique, applied successfully in later studies and allowing the assessment of isoprene SOA, e.g., [33], is thermal desorption aerosol gas chromatography (TAG)/MS, where in situ derivatization using N-methyl-N-(trimethylsilyl)trifluoroacetamide (MSTFA) has been implemented [34].…”
Section: Quantitation Of Isoprene Soa Markersmentioning
confidence: 99%
“…Some studies also suggested that the loading of 2-MTs increased with the enhancement of aerosol acidity (Surratt et al, 2007), and the relative humidity can affect the ratio of 2-MTs to C 5 -alkene triols (Surratt et al, 2010). Recent studies suggested the ratio of 2-MTs to C 5alkene triols decreased with aerosol acidity (Yee et al, 2020), and C 5 -alkene triols were likely formed from thermal degradation of 2-methyltetrol sulfates for GC/MS artifacts (Cui et al, 2018). Hence, it is difficult to explain the different ratios of 2-MTs to C 5 -alkene triols at three heights.…”
Section: Vertical Variations In the Photooxidation Of Bsoa Tracersmentioning
confidence: 99%